Gender and school education: Maintenance or rupture of the binary world? - Fortunato, Ivan (Revista Hipótese, 2022)
This essay seeks elements to better understand the relationship between gender and school education. It is a writing that picks up passages taken from specialized literature, with the aim of tracing the context in which deeper issues about gender, school and teaching can be discussed. Thus, the general objective of this paper is to outline arguments in favor of school education as a form of understanding-reflection-action to combat, perhaps overcome, the woman-man social binarism, generator of so many prejudices and reducing so many Human Rights.